FOOD INCUBATORS FOR SUSTAINABLE DEVELOPMENT OF REGIONS - Zuzana PALKOVÁ; Tibor PALKO (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Food and drink represents the largest manufacturing sector in the EU and encouragingly has sustained positive growth. Even during the economic downturn, levels of employment in the food and drink industry remained quite stable. While the sector has excellent potential for artisan and specialty producers to establish, the lack of access to food grade workspace is a serious and inhibiting barrier to entry. Moreover, artisan food producers struggle to support the capital requirements of setting up a production facility. On the other hand, there is an abundance of underutilized properties in public and private ownership which could be re-imagined as vibrant Food Incubators but the promoters of same lack the skills and practical strategies to develop them. From this point of view, food incubators have the unique potential to spur productive, inclusive and sustainable economic development. They provide a strong foundation for the creation and expansion of food businesses and jobs by helping communities, Vocational Education and Training (VET) bodies, development agencies to revitalise underutilised buildings into powerhouses of food sector learning, innovation and production. The paper presents the project FITR – Food Incubators Transforming Regions, which seeks to forge an effective and replicable model to provide the learning and strategic structure to develop food kitchens and incubators as enterprise, training and support drivers at regional level.